Giving against the Odds: When Tempting Alternatives Increase Willingness to Donate. (February 2015) - Savary, Jennifer; Goldsmith, Kelly; Dhar, Ravi
The authors examine how a reference to an unrelated product in the choice context affects consumers' likelihood of donating to charity. Building on research on self-signaling, the authors predict that consumers are more likely to give when the donation appeal references a hedonic product than when a utilitarian product is referenced or when no comparison is provided. They posit that this phenomenon occurs because referencing a hedonic product during a charitable appeal changes the self-attributions, or self-signaling utility, associated with the choice to donate. A series of hypothetical and actual choice experiments demonstrate the predicted effect and show that the increase in donation rates occurs because the self-attributions signaled by a choice not to donate are more negative in the context of a hedonic reference product. Finally, consistent with these experimental findings, a field experiment shows that referencing a hedonic product during a charitable appeal increases real donation rates in a nonlaboratory setting. The authors discuss the theoretical implications for both consumer decision making and the self-signaling motives behind prosocial choice.